Evaluation method of investment based on real option analysis - Evgeniy Anatolyevich Malyshev; Roman Gennadyevich Podoynitsyn (Экономика региона, 2013)
The article describes the advantages and the procedurefor applying thetheory ofreal options analysis to theevaluation of investment projects. Also describes the disadvantages of traditional methods and attempt to apply the method of real options to the evaluation investments of energy projects. This method is based on the theory of financial options and allows decrease the uncertainty of the future course of events. Our results have demonstrated a new type of real options. This method has been successfully used in assessing the economic efficiency of the third unit Kharanorskaya Power Plant. The research identified a new type of embedded options and calculated parameters. Also, we conclude that the application of the theory of real options analysis in relation to investment projects in energy allows, first, to reduce the uncertainty of the source of information and, consequently, the amount of risk, and second, to evaluate the cost effectiveness of the project in view of the possible solutions in the future, and third, increase the investment attractiveness of the industry. Different companies, investment banks, and other stakeholders can apply the research results as a methodological apparatus evaluating the investment and the possibility to participate in their financing.